2019
DOI: 10.30773/pi.2018.10.23
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Korean Version of the Prodromal Questionnaire-Brief Version in Non-Help-Seeking Individuals

Abstract: Objective In this study, we examined the reliability and validity of the Korean version of the Prodromal Questionnaire-Brief (PQ-B), a self-report screening instrument for clinical high risk for psychosis (CHR). Methods A total of 3,400 middle, high school and college students participated, and 261 subjects with a PQ-B total score ≥3 completed both the PQ-B and the Structured Interview for Prodromal Syndromes (SIPS). Receiver operating characteristic (ROC) curves were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
6
3
1
Order By: Relevance
“…As the participants recruited in this study were college students with an age range of 14 to 31 years, while NAPLS recruited clinician-referred subjects aged 12 to 35 years, SHARP included helpseeking subjects aged 15 to 45 years, and RAP included help-seeking subjects aged 12 to 22 years. Similar to previous studies using PQ-B to screen CHR in Chinese population [16,22,[45][46][47], our research proved that PQ-B could be a feasible rst-step instrument for screening suspected CHR subjects in college students. Both the sensitivity and speci city of PQ-B were excellent in this study.…”
Section: Discussionsupporting
confidence: 85%
“…As the participants recruited in this study were college students with an age range of 14 to 31 years, while NAPLS recruited clinician-referred subjects aged 12 to 35 years, SHARP included helpseeking subjects aged 15 to 45 years, and RAP included help-seeking subjects aged 12 to 22 years. Similar to previous studies using PQ-B to screen CHR in Chinese population [16,22,[45][46][47], our research proved that PQ-B could be a feasible rst-step instrument for screening suspected CHR subjects in college students. Both the sensitivity and speci city of PQ-B were excellent in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Similar to previous studies using PQ-B to screen CHR in Chinese population [16,22,[45][46][47], our research proved that PQ-B could be a feasible rst-step tool to detect suspected CHR subjects in college students.…”
Section: Discussionsupporting
confidence: 85%
“…7 This suggests that the process used in the current study was credible and showed the stability of the mKPQ-16 as a screening tool. The sensitivities and specificities of the PQ-16, PQ-B, and ESI were below 80% in previous studies, 6,7,10 but those of the CAPE-15 in this study were 91.7% and 85.2%, respectively. The AUROC and PPV were higher for the CAPE-15 than for the mKPQ-16.…”
Section: Discussioncontrasting
confidence: 76%
“…In this study, the PPV of the CAPE-15 distress score was improved (32.4%) compared with previous screening tools, 6,7,10 but it was still relatively low for a screening tool with strong predictive power. Nevertheless, when a tool is used to screen for a serious, low-prevalence disease, such as psychosis, the chosen cutoff point should provide good sensitivity, even when the PPV is low or the false-positive rate is high.…”
Section: Discussionmentioning
confidence: 49%